Pengaruh Model Pembelajaran Flipped Classroom Pada Pembelajaran Menulis Karya Imiah Siswa Kelas XI dalam Upaya Meningkatkan Self Improvement di Era New Normal - Rahmawati, Ira; Triyadi, Slamet; Rosalina, Sinta (Peneliti.net, 2023)
The aim of this research is to determine the effect of the learning model applied, namely the flipped classroom learning model, on learning to write scientific papers in an effort to increase the self-improvement of class XI students. The author uses a quantitative approach with a quasi-experimental method. The research design used was the Pre-Experimental method in the form of